Revision of Argentinian species of Hexacola Foerster (Hymenoptera: Figitidae: Eucoilinae) - Reche, Vanina Anadina (2015)
Fil: Reche, Vanina Anadina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Entomología Museo de La Plata; Argentina